New Approach in the Fault Tolerant Control of Three-Phase Inverter Fed Induction Motor - Boumous, Z.; Boumous, S. (Engineering, Technology & Applied Science Research, 2020)
This article provides an improved fault-tolerant control scheme for inverter-powered induction motors. The proposed strategy addresses the cancellation of power switch failures (IGBTs) regardless of their location in a reconfigurable induction motor control. The proposed fault-tolerant topology requires only minimal hardware modifications of the conventional six-switch three-phase drive, mitigating IGBT failures through reconfiguration based on the substitution of an entire inverter arm. The detection mechanism is based on the tridimensional method from which a database will be used for the learning of the neural network. In this method, the current from the stator is used as input to the system, so access to the induction motor is not necessary.